Investigating of the Effective Factors on Housing Prices in district of Laleh Park, Tehran - ali shamai; mahsa delfannasab; mohammad porakrami (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to investigate the factors affecting housing prices in the Laleh Park district of Tehran. In this study, the data of all real estate traded in the first six months of the year 2016 was used in the study area. Information about the physical properties of the residential units trained is collected from the Real Estate Market Information System of Iran and is used to obtain information on the accessibility features of residential units traded using ARC GIS software. Multivariate regression analysis has also been used to investigate the factors affecting housing prices. The results of this study showed that the physical factors of housing are more effective than the access factors in the housing prices in this district . Among the selected features, the variables of residential area, parking, and skeletal type had the most positive effect on the price of housing in the area under study. On the other hand, some of the features, such as the distance from the residential unit to the nearest main street, the residential unit to the nearest educational user, the residential unit distance to the nearest health care provider, and the residential unit's age, had a negative effect on the housing price in the Laleh Park district .